Mercury accumulation in Lethrinus nebulosus from the marine waters of the Qatar EEZ. Issue 1 (15th August 2017) - Al-Ansari, Ebrahim M.A.S.; Abdel-Moati, Mohamed A.R.; Yigiterhan, Oguz; Al-Maslamani, Ibrahim; Soliman, Yousria; Rowe, Gilbert T.; Wade, Terry L.; Al-Shaikh, Ismail M.; Helmi, Ahmed; Kuklyte, Ligita; Chatting, Mark; Al-Ansi Al-Yafei, Mehsin A.
Abstract: Total mercury (THg) and methylmercury (MeHg) were recorded in the commercial demersal fish Lethrinus nebulosus, caught from six locations in Qatar EEZ (Exclusive Economic Zone). Concentrations of THg decreased in the order: liver ˃ muscle ˃ gonad. THg concentrations in fish tissue ranged from 0.016 ppm in gonad to 0.855 ppm (mg kg − 1  w/w) in liver tissues, while concentrations in muscle tissue ranged from 0.24 to 0.49 ppm (mg kg − 1  w/w) among sampling sites. MeHg concentrations were used to validate food web transfer rate calculations. Intake rates were calculated to assess the potential health impact of the fish consumption. There is no major threat to human health from the presence of Hg in L. nebulosus, based upon reasonable consumption patterns, limited to no more than three meals of L. nebulosus per week. Highlights: Hg in fish was within allowable concentrations and poses no threat to public health. Concentrations of Hg decreased in the order: liver ˃ muscle ˃ gonad. Consumers are encouraged to limit themselves to no more than three meals of Sha'ri per week. Eating small fish would be safer than larger and older ones.